Usulan Peningkatan Kualitas Produk Urea dengan Metode Six Sigma Pada PT. XYZ - Bayu Ferdiansyah; Akhmad Wasiur Rizqi; Yanuar Pandu Negoro (Jurnal Serambi Engineering, 2023)
PT. XYZ is a manufacturing company that produces urea fertilizer. The quality of urea fertilizer is influenced by three main parameters, namely H2O content, Biuret, and color. Based on known secondary data in the form of product defect history, in September 2023 product defects will be 12.9%. This research was conducted using the Six Sigma method with the aim of improving overall quality so as to prevent losses in company productivity. The research results show that in the defect category the H2O parameter has a DPMO value of 225834.7 with a sigma value of 2.25, for the biuret parameter it has a sigma value of 2.83 with a DPMO of 91216.7, and for the color parameter it is known that the DPMO value is 562700 or a sigma value of 1.34. then a root cause analysis is carried out using a fishbone diagram to obtain suggestions for improvement. Suggestions for improving Urea Fertilizer products for CTQ H2O include providing training/certification, coordinating with the Utilities section regarding steam, determining the right sampling point, and optimizing vacuum performance. For CTQ Biuret, namely providing training/certification, changing the tonnage in the urea process, paying attention to residence time and controlling the valve to work properly. For CTQ Color, namely providing training/certification, routinely cleaning dye spray filters, determining the right sampling point and routine pump maintenance.